2020
DOI: 10.3390/ma13081896
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of N, C, Cr, and Nb Content on Silicon Nitride Coatings for Joint Applications

Abstract: Ceramic coatings deposited on orthopedic implants are an alternative to achieve and maintain high wear resistance of the metallic device, and simultaneously allow for a reduction in metal ion release. Silicon nitride based (SiNx) coatings deposited by high power impulse magnetron sputtering (HiPIMS) have shown potential for use in joint replacements, as a result of an improved chemical stability in combination with a good adhesion. This study investigated the effect of N, C, Cr, and Nb content on the tribocorr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In one of our previous studies, Filho et al investigated the influence of bias voltage and substrate rotation on the performance of silicon nitride coatings deposited by reactive high-power impulse magnetron sputtering (rHiPIMS) [12]. Based on the results that 1-fold rotation exhibited higher density, the effect of coating density and additional alloying elements (Cr, Nb) on the tribological and corrosion properties of the coatings were further explored and found that while the coatings with higher density exhibited better tribological performance, there was no relationship between the alloy compositions investigated and their wear resistance [13,14]. In order to further investigate the effect of alloying elements, Skjöldebrand et al evaluated compositional gradients of Si-Fe-C-N coatings, finding that the mechanical properties decreased with increasing Fe content but that the coatings showed good biocompatibility with pre-osteogenic MC3T3 cells adhering to the coatings [15].…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous studies, Filho et al investigated the influence of bias voltage and substrate rotation on the performance of silicon nitride coatings deposited by reactive high-power impulse magnetron sputtering (rHiPIMS) [12]. Based on the results that 1-fold rotation exhibited higher density, the effect of coating density and additional alloying elements (Cr, Nb) on the tribological and corrosion properties of the coatings were further explored and found that while the coatings with higher density exhibited better tribological performance, there was no relationship between the alloy compositions investigated and their wear resistance [13,14]. In order to further investigate the effect of alloying elements, Skjöldebrand et al evaluated compositional gradients of Si-Fe-C-N coatings, finding that the mechanical properties decreased with increasing Fe content but that the coatings showed good biocompatibility with pre-osteogenic MC3T3 cells adhering to the coatings [15].…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic implant infection is a very serious issue that can lead to loosening and failure of implants and even cause serious consequences such as a requirement for a second surgery or amputation. Bacterial adhesion, proliferation, and consequent biofilm growth are of particular concern for implant infections. , Although titanium-based implants commonly used in the orthopedic field have good biocompatibility, these materials lack antibacterial activity, and there are problems such as stress shielding and release of harmful metal ions after implantation in vivo. Therefore, recent research has concentrated on seeking substitute materials to overcome these limitations. The polyaryletherketone (PAEK) family of high-temperature thermoplastic polymers has attracted a significant amount of interest for use as orthopedic implant biomaterial because of its suitable elastic modulus value akin to that of bone and its superior chemical stability. Polyetheretherketone (PEEK) and polyetherketoneketone (PEKK) are representatives of the PAEK family .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been studying the application of various protective layers to alleviate wear and corrosion on orthopedic implants in order to increase their lifespan since the 1990s [24,25]. Nitride coatings including silicon nitrides [26][27][28] and superlattice coatings, which are coatings with multiple alternating nitride layers in nanometer scale [29][30][31], are studied most extensively for biomedical applications. An effective coating must be uniform, corrosion resistant and bond strongly to its substrate.…”
Section: Introductionmentioning
confidence: 99%